2017
DOI: 10.1080/00918369.2017.1411693
|View full text |Cite
|
Sign up to set email alerts
|

“She Finally Smiles … for Real”: Reducing Depressive Symptoms and Bolstering Resilience Through a Camp Intervention for LGBTQ Youth

Abstract: While summer camps are a recognized evidence-based strategy for building social and emotional skills among youth (U.S. Centers for Disease Control and Prevention [CDC], 2009), no known studies have evaluated the effects of camp programming for LGBTQ youth in the United States. This pilot study evaluates a novel program (Brave Trails) for LGBTQ youth ages 12 to 20, using a pre-post camper survey (N = 56) and a post-camp parent survey (N = 54). Results show campers experienced increases in identity affirmation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…This includes those who have "transitioned," those who happen to express their gender differently than others, and those who may experience teasing or bullying because of their gender. (Camp Aranu'tiq, 2018a) Besides Camp Aranu'tiq, a handful of other camps offer sessions just for lesbian, gay, bisexual, trans, and queer (LGBTQ+) youth, such as Camp Brave Trails (cf., Gillig, Miller, & Cox, 2017), that provide a safe space with people who share similar life experiences to help mitigate their potential feelings of isolation.…”
Section: Camps Serving Transgender Youthmentioning
confidence: 99%
“…This includes those who have "transitioned," those who happen to express their gender differently than others, and those who may experience teasing or bullying because of their gender. (Camp Aranu'tiq, 2018a) Besides Camp Aranu'tiq, a handful of other camps offer sessions just for lesbian, gay, bisexual, trans, and queer (LGBTQ+) youth, such as Camp Brave Trails (cf., Gillig, Miller, & Cox, 2017), that provide a safe space with people who share similar life experiences to help mitigate their potential feelings of isolation.…”
Section: Camps Serving Transgender Youthmentioning
confidence: 99%
“…While admirable, this approach does not necessarily reflect the realities of the heteronormative social structure and LGBTQ oppression. Further, research supports that LGBTQ-focused programs can positively influence outcomes for this population (Gillig, Miller, & Cox, 2017;Jarvis, 2015;Krane, Barber, & McClung, 2002;Ravel & Rail, 2006).…”
Section: Discussionmentioning
confidence: 92%
“…(4) Research speci cally examining resilience and the role of social support in the lives of transgender youth is currently lacking, with few exceptions, (13,14) and very few interventions have been tested. (7,8) The Minority Stress Model, (10) and GMSR, (11) informed the development of Pride Camp as an intervention for LGBTQ youth. The goal was to create an a rming environment that offered experiences of community connectedness, social support, pride, as well as opportunities to learn coping and resilience…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…7Gillig, Miller, and Cox describe the impact of another intervention called Brave Trails, an outdoor summer camp model, adapted speci cally for building strengths and reducing depressive symptoms in LGBTQ youth ages 12-20, and the rst camp for LGBTQ youth in the United States. (8) In an uncontrolled pilot test, they found that campers (n = 56) reported increased hope, identity a rmation, and a reduction in depressive symptoms, from pre to post test. They also administered a parent survey and found that parents perceived similar positive changes in their children after attending camp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation